Soluble immune checkpoint proteins as predictive biomarkers for lymph node metastases in penile cancer - Glombik, Dominik; Carlsson, Jessica; Kirrander, Peter; Davidsson, Sabina (Frontiers in Immunology, 2026)
BackgroundPenile cancer (PeCa) is a rare but aggressive disease where lymph node metastases (LNM) represent the most significant prognostic factor. Accurate identification of LNM remains a clinical priority, but traditional imaging and clinical parameters often fail to detect occult LNM. Soluble immune checkpoint proteins (sICs) have recently emerged as potential non-invasive biomarkers in various malignancies, although unexplored in PeCa. The primary aim of this study was to explore the value of a panel of 14 sICs for predicting LNM in PeCa. The secondary aim was to compare plasma sIC levels between PeCa patients and cancer-free controls.MethodsUsing ProcartaPlex immunoassays, BTLA, IDO, LAG-3, HVEM, PD-1, PD-L1, PD-L2, TIM-3, CD80, CTLA-4, GITR, CD27, CD28, and CD137 were measured in plasma from 284 PeCa patients and 45 cancer-free controls. PeCa patients were divided into a training set (n=202) and a test set (n=82). A prediction model for LNM was created using logistic regression.ResultsOverall accuracy of the prediction model reached 77.5% (95% CI: 70.9 - 83.3) for the training set, yielding 8.9% sensitivity and 99.3% specificity in predicting LNM. Upon validation using the test set, the accuracy decreased to 62.2% (95% CI: 50.8-72.7) with 17.9% sensitivity and 85.2% specificity. When comparing PeCa patients and cancer-free controls, four inhibitory sICs (IDO, TIM-3, CD80, and CTLA-4) were found at significantly higher levels in the PeCa group. Due to the rarity of the disease, the main limitation of the study is the small number of patients with LNM.ConclusionOur study provides no evidence that sICs can predict LNM in PeCa, although four inhibitory sICs were significantly elevated in PeCa patients compared to cancer-free controls, suggesting systemic immunosuppression associated with tumor presence, consistent with findings in other malignancies. Studies with larger cohorts are warranted to clarify the prognostic significance of sICs in PeCa.